Expression of RONIN and NANOG-associated proteins in goat parthenogenetic embryos - Moura, Marcelo Tigre; Ramos-Deus, Pamela; Ferreira-Silva, José Carlos; Corrêa Silva, Priscila Germany; Cantanhêde, Ludymila Furtado; Nascimento, Pábola Santos; Silva, Roberta Lane Oliveira; Benko-Iseppon, Ana Maria; Oliveira, Marcos Antonio Lemos (Medicina Veterinária, 2017)
The expression of a subset of transcription factors is enriched in early preimplantation embryos, which contributes to their cellular plasticity. RONIN, NANOG and its associated proteins are PluripotencyAssociated Transcription Factors (PATF) that control relevant downstream pathways in pluripotent stem cells, but their activity in early embryos remained less understood. The work was aimed to determine the expression of RONIN and four NANOG-associated PATFs in goat preimplantation embryos. Goat embryos were produced in vitro by parthenogenetic activation. Gene transcripts of cleavage-stage embryos were investigated by reverse transcriptase-polymerase chain reaction (RT-PCR), while blastocysts were analyzed by both RTPCR and quantitative RT-PCR (RT-qPCR) assays. Gene transcripts of ZFP281, NAC1, and NR0B1 were detected in cleavage-stage embryos, while RONIN and OCT4 were not found expressed. Detection in blastocysts by RT-PCR confirmed the activity of NR0B1, RONIN, and OCT4. Moreover, all five PATF were detected in blastocysts by RT-qPCR (ZFP281, NAC1, RONIN, OCT4, and NR0B1). In conclusion, RONIN and NANOG-associated proteins are active during goat parthenogenetic preimplantation development and hold stage-specific expression patterns.